Relation between Soluble CD14 Levels, Inflammation, Subclinical Atherosclerosis and Mortality in Hemodialysis Patients - Abdallah, Amany M.; Elhakeem, Heba; Yahia, Mohamed Basiouny; Youssef, Eman M. I.; El-Khouly, Nashwa; Elmohaseb, Ghada Fathy; Awad, Eman Abu-Elnasr; Hassan, Marwa Mohamed; Ghamry, Esam Mohamed; Abdelhamed, Mohamed Rashed; Kotb, Essam; Mahmoud, Tamer Mohamed (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2023)
Background and Aim: Chronic kidney disease (CKD) is characterized by persistent lowgrade inflammation. Soluble CD14 (sCD14) is involved in many pathological conditions, including inflammation and atherosclerosis. The present study aimed to assess the relationship between sCD14 levels, subclinical atherosclerosis (SCA), inflammation and mortality in Egyptian hemodialysis (HD) patients. Patients and Methods: The present longitudinal study included 62 HD patients. All patients were submitted to careful history taking, thorough clinical examination and laboratory assessment for high-sensitivity C-reactive protein (hsCRP) and sCD14. Carotid intima-media thickness (CIMT) was also assessed. Patients were followed for a maximum of 18 months. The primary outcome is patients’ mortality. Data were statistically analyzed using standard descriptive, comparative, correlative and regression methods. Results: The present study was conducted on 62 HD patients. They comprised 34 males and 28 females with an age of 54.6 ± 9.0 years. At the end of follow-up, 12 patients (19.4 %) died. It was shown that survivors had significantly lower hsCRP levels (104.2 ± 38.2 versus 134.1 ± 15.3 mg/dL, p < 0.001), lower sCD14 levels (32.7 ± 10.3 versus 47.4 ± 18.4 μg/mL, p = 0.02) and lower CIMT (1.32 ± 0.5 versus 1.5 ± 0.2 mm, p = 0.049). sCD14 levels were significantly correlated with hsCRP (r = 0.4, p = 0.001) and CIMT (r = 0.31, p = 0.013). Multivariate analysis identified HD duration [HR (95% CI): 1.02 (1.0-1.04), p = 0.021] and sCD14 levels [HR (95% CI): 1.06 (1.0-1.12), p = 0.026] as significant predictors of patients’ survival. Conclusions: sCD14 levels in this cohort of HD patients are well-correlated with hsCRP levels and CIMT. In addition, they are significant predictors of patients’ mortality.
Keywords: hsCRP